Hybrid approaches to teaching: Re-imagining the teaching of a foundational science course during a global pandemic - Parker, Daniel; Vorster, Jo-Anne; Quinn, Lynn; Blackie, Margaret (Critical Studies in Teaching and Learning, 2023)
Access to scientific knowledge, and teaching in the sciences, is believed to be about training because scientific knowledge is, generally, specialised. However, for students to gain full epistemological access in the sciences, they also need to be inducted as scientists and learners of science. We use Bernstein’s regulative and instructional discourse to engage with the notion of epistemological access and effectiveness of a foundational science course. We examine how the course can cultivate scientific identities amongst first year students at a recently established South African university. Our analysis assesses the impact of the forced shift from contact teaching to Emergency Remote Teaching due to the COVID-19 pandemic. We demonstrate that the course was able to begin to facilitate the cultivation of different kinds of knowers in science. However, several gaps remain. Thus, we argue that foundational science lecturers should focus on hybrid teaching approaches to promote enhanced learning amongst students.